Re-examination of the Base Miocene Unconformity in west Sabah, Malaysia, and stratigraphic evidence against a slab-pull subduction model - Lunt, P. (Elsevier Ltd, 2022)
This review chiefly examines data on the regionally important Base Miocene Unconformity, confirming its age and expression in west Sabah, then integrates this with data on the tectono-stratigraphic development of the broader Sabah to Palawan region. The two unconformities described (the Base Miocene Unconformity and the younger Deep Regional Unconformity) were both produced when deformation abruptly stopped, leaving erosional surfaces that were then transgressed. The ages of these two events are c. 24 and 12â13 Ma respectively, and the areas affected by the prior uplift and erosion can be mapped. The results are incompatible with widely cited plate tectonic models that describe closure of a postulated Proto-South China Sea PSCS. These prior models had assumed plate drift ended with collision at plate docking over a PSCS suture in about mid Early Miocene times. However, stratigraphic data shows that Early Miocene times were a period of quiescence across Sabah, with mostly mild subsidence. It is therefore proposed that plate drift in the SCS could not have been linked to any type of subduction process anywhere around western Sabah. The absence of any plate docking or any Oligocene through Middle Miocene compression around northern Palawan is a further anomaly to the old subduction based tectonic model. Â© 2022